2008
DOI: 10.1186/1471-2490-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of three immunohistochemically detected markers of neuroendocrine differentiation with clinical predictors of disease progression in prostate cancer

Abstract: BackgroundThe importance of immuno-histological detection of neuroendocrine differentiation in prostatic adenocarcinoma with respect to disease at presentation and Gleason grade is gaining acceptance. There is limited literature on the relative significance of three commonly used markers of NE differentiation i.e. Chromogranin A (CgA), Neuron specific enolase (NSE) and Synaptophysin (Syn). In the current work we have assessed the correlation of immuno-histological detection of neuroendocrine differentiation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…Serum chromogranin A, a NE differentiation marker, has been proposed as an indicator of advanced prostate cancer in some patients who do not have elevated serum PSA. 8,[33][34][35] In the present study, by analyzing molecular pathways altered during NE differentiation, we have identified a small cluster of putative predictive markers that could identify PC at high risk of resistance to therapy and might serve as therapeutic targets for prevention and to slow disease progression. AKT, an important signaling molecule in mammalian cells, is considered a key player in many tumors including PC 36 and transgenic mice expressing activated AKT in the prostate develop intraepithelial neoplasia, 37 a precursor lesion of PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum chromogranin A, a NE differentiation marker, has been proposed as an indicator of advanced prostate cancer in some patients who do not have elevated serum PSA. 8,[33][34][35] In the present study, by analyzing molecular pathways altered during NE differentiation, we have identified a small cluster of putative predictive markers that could identify PC at high risk of resistance to therapy and might serve as therapeutic targets for prevention and to slow disease progression. AKT, an important signaling molecule in mammalian cells, is considered a key player in many tumors including PC 36 and transgenic mice expressing activated AKT in the prostate develop intraepithelial neoplasia, 37 a precursor lesion of PC.…”
Section: Discussionmentioning
confidence: 99%
“…7 The importance of immuno-histological detection of NED in prostatic adenocarcinoma with respect to disease at presentation and Gleason grade is gaining acceptance, and a correlation of immunohistochemically detected markers of neuroendocrine differentiation with clinical predictors of disease progression in prostate cancer has been reported. 8 Using proteomic analysis of the nuclear matrix, we previously reported that hnRNP K, a member of the hnRNP family with pleiotropic functions, 9-12 was overexpressed in PC specimens with involvement of seminal vesicles and that its expression level was closely correlated with Gleason score …”
mentioning
confidence: 99%
“…In 84 prostate cancer patients, Ather et al evaluated the correlation of immunohistological detection of neuroendocrine differention marker NSE with Gleason grade. They found that NSE had a significantly higher expression with worsening Gleason grade (Ather et al, 2008). Humez et al (2006) observed that neuroendocrine differentiation was associated with NSE expression and this was important for the prostate cancer progression and hormonal-therapy failure.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of these markers has been analyzed in several studies; CgA and NSE were shown to have an independent prognostic significance in prostate cancer [22]. CgA appears to be the best sensitive marker for detecting NE differentiation [22]. Ferrero-Poüs et al [23] found that patients resistant to androgen-suppressive treatments and with elevated PSA had an increase in CgA and NSE in 62 and 29% of cases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of NE markers might reflect the NE activity of prostate carcinoma [21]. The clinical significance of these markers has been analyzed in several studies; CgA and NSE were shown to have an independent prognostic significance in prostate cancer [22]. CgA appears to be the best sensitive marker for detecting NE differentiation [22].…”
Section: Introductionmentioning
confidence: 99%